Comparative Immunogenicity of Several Enhanced Influenza Vaccine Options for Older Adults: A Randomized, Controlled Trial. (12th December 2019) - Cowling, Benjamin J; Perera, Ranawaka A P M; Valkenburg, Sophie A; Leung, Nancy H L; Iuliano, A Danielle; Tam, Yat Hung; Wong, Jennifer H F; Fang, Vicky J; Li, Athena P Y; So, Hau Chi; Ip, Dennis K M; Azziz-Baumgartner, Eduardo; et al.
Abstract: Background: Enhanced influenza vaccines may improve protection for older adults, but comparative immunogenicity data are limited. Our objective was to examine immune responses to enhanced influenza vaccines, compared to standard-dose vaccines, in community-dwelling older adults. Methods: Community-dwelling older adults aged 65–82 years in Hong Kong were randomly allocated (October 2017–January 2018) to receive 2017–2018 Northern hemisphere formulations of a standard-dose quadrivalent vaccine, MF59-adjuvanted trivalent vaccine, high-dose trivalent vaccine, or recombinant-hemagglutinin (rHA) quadrivalent vaccine. Sera collected from 200 recipients of each vaccine before and at 30-days postvaccination were assessed for antibodies to egg-propagated vaccine strains by hemagglutination inhibition (HAI) and to cell-propagated A/Hong Kong/4801/2014(H3N2) virus by microneutralization (MN). Influenza-specific CD4 + and CD8 + T cell responses were assessed in 20 participants per group. Results: Mean fold rises (MFR) in HAI titers to egg-propagated A(H1N1) and A(H3N2) and the MFR in MN to cell-propagated A(H3N2) were statistically significantly higher in the enhanced vaccine groups, compared to the standard-dose vaccine. The MFR in MN to cell-propagated A(H3N2) was highest among rHA recipients (4.7), followed by high-dose (3.4) and MF59-adjuvanted (2.9) recipients, compared to standard-dose recipients (2.3). Similarly, the ratio of postvaccination MN titers among rHA recipients to cell-propagated A(H3N2) recipients was 2.57-fold higher than the standard-dose vaccine, which was statistically higher than the high-dose (1.33-fold) and MF59-adjuvanted (1.43-fold) recipient ratios. Enhanced vaccines also resulted in the boosting of T-cell responses. Conclusions: In this head-to-head comparison, older adults receiving enhanced vaccines showed improved humoral and cell-mediated immune responses, compared to standard-dose vaccine recipients. Clinical Trials Registration: NCT03330132. Abstract : In this randomized, controlled trial, we evaluated the immunogenicity of enhanced influenza vaccines and found that older adults receiving enhanced vaccines showed improved humoral and cell-mediated immune responses, compared to standard-dose vaccine recipients.